Pengaruh Digitalisasi Pajak, Tax Amnesty, dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak: Studi Kasus Wajib Pajak Orang Pribadi di Kantor Pelayanan Pajak (KPP) Surabaya Mulyorejo - Elma Liyanty Putri; Anik Yuliati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The role of taxes is very important in the administration of the government and the draft of the State Budget (APBN), this is because taxes are the largest source of state revenue, which contributes 80% of total state revenue. Therefore, the government does many ways to optimize tax revenue and taxpayer compliance. This study aims to analyze the effect of tax digitalization, tax amnesty, and tax sanctions on individual taxpayer compliance at KPP Pratama Surabaya Mulyorejo. This research was conducted by quantitative methods and used primary data objects obtained from the distribution of questionnaires as many as 100 respondents. The object of research is a non-employee individual taxpayer registered at KPP Surabaya Mulyorejo. To analyze the data, multiple linear regression was used with the help of SPSS Version 25 software. The results showed that tax digitalization did not affect the compliance of non-employee individual taxpayers registered at KPP Surabaya Mulyorejo. Tax amnesty has a positive effect on the compliance of non-employee individual taxpayers registered at KPP Surabaya Mulyorejo. Tax sanctions have no effect on the compliance of non-employee individual taxpayers registered at KPP Surabaya Mulyorejo.